High false positives and false negatives in yeast parameter in an automated urine sediment analyzer - Aydin Ozgur; Yasar Ellidag Hamit; Eren Esin; Yilmaz Necat (Journal of Medical Biochemistry, 2015)
Background: Automated urine sediment analyzers have proven their feasibility in medical laboratories. However, editing manual microscopic review of some specimens severely limits the usefulness of such systems. This study aims to give feedback on the practical experience on "Yeast", which is one of the parameters that compel frequent manual reviews. Methods: 5448 freshly collected urine specimens submitted from various departments of our hospital for diagnostic urinalysis were studied by the UriSed® (77 Elektronika, Hungary). A specialist medical doctor inspected every image on-board, and reviewed the ones with a "Yeast" alarm by traditional manual microscopy. Results: UriSed alarmed in 491 samples (9%) for yeast. In 59 samples (1%) the number of particles exceeded the cut-off and a "positive for yeast" was set. A false positive report of yeast +1 to 3+/H PF was found in 51 samples (0.9%). There were 8 cases with positive for yeast from both microscopic methods. Thirty-three "negative for yeast" samples were corrected as positive after the manual microscopic review. Conclusions: We report a high percentage of false positives and negatives in the yeast parameter, in line with other studies on UriSed as well as on other instruments in the market. As an important feedback, our observations showed that the major concern in false results was "the focusing problem". We believe in the necessity of a focus check and comparison of alarms between images on board.